Teachers' identification of exceptional children and a study of the teaching strategies which they adopt to meet the needs of these groups of people - Kerry, Trevor (1982)
This thesis sets out to examine how teachers cater for the bright pupils and slow learners in first year mixed ability classes in five comprehensive schools. Teachers were asked to nominate bright pupils and slow learners in their classes using categories on a class profile instrument. The same teachers were observed teaching these classes. Observations covered most academic subjects on the timetable: RE, French, science, history, English, mathematics, geography, music and integrated studies. Over a period of a month the teachers' talk and questions, the pupils' responses, and the tasks set to pupils were each analysed for cognitive demand using specially adapted or newly devised instruments. The study suggests that very little cognitive stimulation takes place in these first year mixed ability groups. Most verbal transactions have to do with class management, and of the remainder the majority are information-giving or information-seeking. Tasks, too, are mainly of a lower cognitive order. In only two of the five schools did it appear that teachers made significantly higher cognitive demands on the perceived bright pupils than on other pupils. Though there is some evidence to suggest that bright pupils and slow learners may receive a disproportionately large amount of interaction with teachers, there was virtually no evidence to suggest that teachers tailor tasks or teaching strategies to cater specifically for the needs of these two groups in a mixed ability context. Most teaching is undifferentiated whole-class teaching aimed at all the pupils and not at individuals. Some small-scale comparative studies were carried out in banded groups, and also in a primary school, a middle school, and in an accelerated set leading to GCE 101 level examinations in the 4th year. An important outcome of the thesis is the development of an Analysis of Classroom Tasks proforma for the secondary school. The size and scope of the main study, covering over 200 single periods by 36 teachers in 8 subject disciplines, suggests that the results may have some degree of generalizability.